Reduced home advantage for basketball teams from capital cities in Europe - Gomez, M. A.; Pollard, R. (European Journal of Sport Science, 2011)
The aim of the present study was to investigate the home advantage effect in professional basketball leagues in Europe, especially the differences in home advantage between capital city teams and other teams in each country. All the teams (n=159) of seven national professional basketball leagues were studied (Bulgaria, Greece, Lithuania, Romania, Russia, Spain, and Turkey) and classified as capital city teams or other teams. The data (n=7432 games) were gathered for six seasons (2003-2004 to 2008-2009). The results confirmed the existence of a home advantage effect in all seven basketball leagues. There was a significant difference (P<0.001) between the leagues, with home advantage highest in Romania (65.10%) and Greece (65.02%), and lowest in Turkey (58.12%) and Lithuania (56.13%). The results also show that capital city teams experienced lower home advantage compared with other teams in all seven countries. After controlling for team ability, this was statistically significant for Bulgaria, Greece, Romania, and Turkey (all P<0.05), but not for Lithuania, Russia or Spain (all P>0.10). These results are consistent with previous studies in football, which suggested that teams playing in capital cities in Europe had lower home advantage than those playing elsewhere. Possible reasons for this finding include a diminished sense of being part of a cohesive local community when playing in a capital city, a lower sense of territorial protection and, for the away team, a lessened feeling of unfamiliarity.